A Practical Guide in Designing Curriculum for Diverse Learners - Muhamad Ario Setiawan; Zaitun Qamariah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The increasing diversity in the student population presents challenges for educators in designing curricula that cater to the needs of all learners. This article explores the importance of designing curricula for diverse learners and the benefits it brings in promoting educational equity and inclusive education. It emphasizes the need to recognize and respect learners' diverse backgrounds, abilities, and learning styles to create an environment that fosters equal opportunities and educational success. Library research was conducted to gather information on designing curriculum for diverse learners. Thorough literature searches were performed using online library catalogs, research databases, and academic journals. Relevant sources were critically evaluated for credibility and relevance to ensure reliable information.The article discusses the needs of diverse learners, the challenges in curriculum design, frameworks and models for designing curriculum, and strategies to adapt the curriculum to meet diverse learners' needs. It highlights the significance of understanding cultural backgrounds, language proficiency, learning styles, abilities, and equitable access to resources. The Universal Design for Learning framework and other models offer valuable strategies for inclusive curriculum design.